Current Status and Transformation of Satellite Navigation Industry Policies in China - Yang Junlin (《中国工程科学》杂志社, 2021)
Satellite navigation is an emerging industry of strategic importance in China. Targeted and powerful industrial policies can help optimize and upgrade the satellite navigation industry and promote the scaled, industrialized, and international development of the BeiDou Navigation Satellite System. They can also help establish a comprehensive spatiotemporal system that is integrated, ubiquitous, and intelligent. This study focuses on the transformation of China’s satellite navigation industry policies and expounds on the role of industrial policies in the development of the satellite navigation industry. Besides, it also summarizes the current status and main problems of the industry policies at the country, industry, and region levels, and analyzes the objectives, basic ideas, and measures for the transformation of these policies. The study demonstrates that a policy system has been preliminary established for the navigation satellite industry in China. However, the legalization level of the industry policies is low; these policies are fragmented; the policy instruments have not been scientifically combined; targeted policy support is urgently required for the core technology research of the industry; and the application of international rules and standards is inadequate. To promote the high-quality development of the satellite navigation industry in China, we suggest that the legislation of the industry should be accelerated, and policy support and dominating methods for the industry should be adjusted. Moreover, comprehensive and targeted policy implementation should be promoted, the coordination mechanism should be improved, and China’s satellite navigation industry should participate in the formulation of international standards and rules.